The role of ionic liquids in desulfurization of fuels: A review - Ibrahim, M.H.; Hayyan, M.; Hashim, Mohd Ali; Hayyan, Adeeb (Elsevier, 2017)
Sulfur compounds in transportation fuels are a pressing issue currently due to the more stringent limits of sulfur content. Sulfur compounds lead to SOx emissions which cause many environmental and health problems. The conventional refinery desulfurization process, hydrodesulfurization (HDS), is conducted at elevated temperatures and pressures, using expensive hydrogen gas and catalysts. This review aims to discuss the merits and drawbacks of the major areas of alternative desulfurization technologies, including biodesulfurization, adsorption, extractive and oxidative desulfurization, with special emphasis on the role of ionic liquids (ILs) as distinctive multi-task fluids. With the rapid development of ILs in the last decades, more effective and reliable desulfurization techniques are foreseeable.